Peningkatan Desain Promosi UMKM melalui Pelatihan Penggunaan Canva untuk Iklan Produk - Afifah, Sayyidah (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
Micro, small and medium enterprises (MSMEs) play a crucial role in the Indonesian economy, contributing significantly to gross domestic product (GDP) and employment. However, rapidly increasing digitalisation poses new challenges, especially for MSMEs in rural areas, which are often less exposed to digital technology. In an effort to help MSMEs compete in a wider market, this community service programme was conducted in the Teras Ciapus community, Tamansari District, Bogor Regency, with the aim of improving promotional design skills using the Canva application. The training involved 15 (fifteen) participants and included pre-test, training, mentoring and post-test. Through this training, participants were taught basic graphic design techniques, visual communication and a demonstration of how to use Canva as an easily accessible design tool. The results of the training showed a significant improvement in the participants' ability to understand graphic design principles and their ability to use Canva. Participants now feel more capable and confident in using digital design to support the marketing of their MSME products. The training also provided new insights into the importance of adapting to digital technology to expand market access and strengthen the position of local products in the face of competition. The programme not only developed participants' technical skills, but also raised awareness of the benefits of digital promotion as a more effective business strategy.